On V.N. Koshlyakov’s works in mechanics and its applications - Kalinovich, V. N.; Mitropolskiy, Yu. A.; Onishchenko, S. M.; Polishchuk, A. N.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We present a survey of the principal results obtained by V. N. Koshlyakov in analytical mechanics, dynamics of solids, and applied theory of gyroscopes.